Improving Child Health in Sub-Saharan Africa - Three essays in microeconometrics - (:unkn) unknown (My University, 2022)
Ensuring a sufficiently high level of health for every child is both a social justice goal and undoubtedly an essential investment given the extensive empirical evidence on the long-run consequences of early life health on later life outcomes. Despite numerous efforts, the situation still gives cause for concern, especially in Sub-Saharan Africa. Identifying the factors that hinder or slow down child health improvement is thus of primary interest. This thesis is part of the continued efforts to provide empirical evidence to inform public policy. It sheds new light on several issues related to the improvement of the health status of young children, such as access to care, household health behaviors, and the health effects of the construction of economic infrastructures such as water reservoirs, in resource-limited settings. The first chapter shows that the introduction of free primary care in Zambia has led to a substantial increase in maternal health care utilization but has only had limited effects on the health of young children. It also highlights the importance of combining such a policy with improvements in physical access to health facilities and quality of care. The second chapter explores the intergenerational effects of parental education on both health investments and young child health in Zimbabwe. It uncovers an important role of paternal education in improving prevention behaviors in the household. This relationship had previously been largely ignored in the literature. The final chapter examines the health consequences of water reservoir construction in 34 Sub-Saharan African countries. The results suggest the existence of conflicting effects: chronic malnutrition decreases, while exposure to malaria risk increases with proximity to a water reservoir. These results call for complementary policies to mitigate this adverse effect. Particular attention is systematically paid to the identification of causal effects and to the public policy im
Keywords: African Research